Greenhouse gas reduction and improved sustainability of animal husbandry using amino acids in swine, poultry feeds. (9th January 2013) - Tsujimoto, Susumu; Takagi, Tomo; Osada, Takashi; Ogino, Akifumi
Abstract In Annex 1 countries, nitrous oxide (N2O) emissions from swine and poultry excreta have been calculated and the N2O reduction potential of each country by using amino acids in feed could also be calculated, then a comparison made among the countries. The N2O reduction rates were approximately 25% for these Annex 1 countries and amino acids were able to make a large contribution to that reduction. Greenhouse gases (GHG) which are N2O combined with methane (CH4) were estimated to reduce by 24.8% in Japan when amino acids were introduced into the feed, but only a 7.2% reduction was estimated in France. Purification, which is mainly used for manure treatment in Japan, emits much more N2O and less CH4, whereas the liquid system which is mainly used in France emits more CH4 and less N2O based on the emission factors from the United Nations Framework Convention on Climate Change data base. Changing the French manure treatment system to the Japanese style with amino acids in feed would reduce GHG emissions by 23.4%. Reduction of the arable land use in Japan by changing crop formulations supported by adding amino acids to feed was also quantified as about 10% and led to an increase in the production of meat using the same arable land area.